Spinal Cord Resting State Activity in Individuals With Fibromyalgia Who Take Opioids - Martucci, Katherine T.; Weber, Kenneth A.; Mackey, Sean C. (Frontiers in Neurology, 2021)
Chronic pain coincides with myriad functional alterations throughout the brain and spinal cord. While spinal cord mechanisms of chronic pain have been extensively characterized in animal models and in vitro, to date, research in patients with chronic pain has focused only very minimally on the spinal cord. Previously, spinal cord functional magnetic resonance imaging (fMRI) identified regional alterations in spinal cord activity in patients (who were not taking opioids) with fibromyalgia, a chronic pain condition. Here, in patients with fibromyalgia who take opioids (N=15), we compared spinal cord resting-state fMRI data vs patients with fibromyalgia not taking opioids (N=15) and healthy controls (N=14). We hypothesized that the opioid (vs non-opioid) patient group would show greater regional alterations in spinal cord activity (ie, the amplitude of low frequency fluctuations or ALFF, a measure of regional spinal cord activity). However, we found that regional spinal cord activity in the opioid group was more similar to healthy controls, while regional spinal cord activity in the non-opioid group showed more pronounced differences vs healthy controls. Across patient groups, fatigue correlated with regional differences in spinal cord activity. Additionally, spinal cord functional connectivity and graph metrics did not differ among groups. Our findings suggest that, contrary to our main hypothesis, patients with fibromyalgia who take opioids do not have greater alterations in regional spinal cord activity. Thus, regional spinal cord activity may be less imbalanced in patients taking opioids compared to patients not taking opioids.